The Solution of Absolute Value Equations Using Two New Generalized Gauss-Seidel Iteration Methods. (6th May 2022) - Ali, Rashid
Abstract : In this paper, we provide two new generalized Gauss-Seidel (NGGS) iteration methods for solving absolute value equations A x − ∣ x ∣ = b, where A ∈ R n × n, b ∈ R n, and x ∈ R n are unknown solution vectors. Also, convergence results are established under mild assumptions. Eventually, numerical results prove the credibility of our approaches.